Hukum Fundraising Pada Lembaga Filantropi di Indonesia - Faa Izah; Nurhasanah; Rizal Sofyan Gueci (Mavisha: Law and Society Journal, 2025)
Philanthropy is the practice of giving, services, and association as voluntary actions for the public good. Philanthropic organizations in Indonesia have public and private legal forms in carrying out fundraising mechanisms for collecting money or goods in the community. This study aims to determine the implementation of fundraising, harmonization of rules, and legal effectiveness of existing rules. The scope of the research is BAZNAS Jambi province, Aqsa Working Group (AWG), and Medical Emergency Rescue Comittee (MER-C). This research is limited to the scope of philanthropic activities in the form of religious social fundraising. This research uses normative-empirical legal methods with conceptual approaches, legislation, and case studies. The collection method used is normative-empirical law by conducting literature studies, interviews, and examining documents relevant to the research. Meanwhile. The legal theory used as an analytical tool is the theory of legal harmonization and the theory of legal effectiveness. From the research it is concluded that there is disharmonization and insynchronization of laws and regulations, the existence of a legal vacuum, and the absence of legal certainty in philanthropic institutions. The ineffectiveness of the existing rules has caused legal consequences in the form of ineffective implementation of fundraising carried out by philanthropic institutions, differences in fundraising mechanisms between philanthropic institutions, and the emergence of trust issues in the community. Thus, it is necessary to update the legislation regarding fundraising mechanisms in Indonesia.   Abstrak: Filantropi merupakan praktik giving, services, dan association sebagai tindakan sukarela untuk kepentingan publik. Lembaga filantropi di Indonesia memiliki bentuk berbadan hukum publik dan privat dalam menjalankan mekanisme fundraising pengumpulan uang atau barang di masyarakat. Penelitian ini bertujuan untuk mengetahui implementasi fundraising, harmonisasi aturan, dan efektivitas hukum dari aturan yang ada. Adapun ruang lingkup penelitian yaitu BAZNAS provinsi Jambi, Aqsa Working Group (AWG), dan Medical Emergency Rescue Comittee (MER-C). Penelitian ini dibatasi pada ruang lingkup kegiatan filantropi berupa pengumpulan dana sosial keagamaan. Penelitian ini menggunakan metode hukum normatif-empiris dengan metode pendekatan konseptual, peraturan perundang-undangan, dan studi kasus. Metode pengumpulan yang digunakan yaitu hukum normatif-empiris dengan melakukan studi pustaka, wawancara, dan meneliti dokumen yang relevan dengan penelitian. Sementara itu. Teori hukum yang dijadikan sebagai alat analisis ialah teori harmonisasi hukum dan teori efektivitas hukum. Dari penelitian disimpulkan bahwa adanya disharmonisasi dan insinkronisasi peraturan perundang-undangan, adanya kekosongan hukum, serta tidak adanya kepastian hukum pada lembaga filantropi. Belum efektifnya aturan yang ada menimbulkan akibat hukum berupa tidak efektifnya pelaksanaan fundraising yang dijalankan lembaga filantropi, adanya perbedaan mekanisme fundraising antar lembaga filantropi, dan timbulnya trust issue di masyarakat. Sehingga, perlu adanya pembaruan peraturan perundang-undangan mengenai mekanisme fundraising di Indonesia.